Pengembangan Inovasi Pembelajaran Berbasis Proyek Ilmiah dalam Meningkatkan Sikap terhadap Ilmu Pengetahuan Siswa SMP Kota Malang - Novi Anisa Hidayati; Nata Hendriati; Puguh Prasetyo; Hendryani A. Putri; Siti Maimunah (Jurnal Konseling dan Pendidikan)
One of Indonesian national education goals is to educate the intellectual life of the nation which is embodied in the preamble of the 1945 Constitution. Education plays a very central role to facilitate students to prepare the demands of science and technology advancement in the 21st century. To achieve these goals, education requires a powerful learning methods which can improve the positive attitude toward science of student from an early age. This study aims to determine the differences in attitude toward science between students in experimental group who received projects based learning and students who become the control group. This was quasy experimental research with Pretest-Postest Control Group Design. The populations were VIII graders in Malang city. The sampling was 54 student selected using purposive sampling. Instruments were validated by expert and tried out. The reliability coefficients for attitude toward science scale was 0,954. The results showed that attitude toward science students in experimental group who received projects based learning has significant difference with students in control group.